Hubungan Dukungan Sosial Dengan Psychological Well-Being Pada Mahasiswa Tingkat Akhir Di Kota Bukittinggi - Putri, Aisha; Aviani, Yolivia Irna (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
Research with the aim of seeing the correlation between social support and psychological well-being was carried out on final year students studying in Bukittinggi City. The research method is a questionnaire with a quantitative approach used in this research. A total of 285 final year students in Bukittinggi City were the research samples. Samples were obtained using cluster random sampling technique. The research results show an r value = 0.781 and a p value = 0.000, where Ha is accepted. Instrument reliability test for social support variables = 0.857 and PWB = 0.878. The results showed that there was a significant positive relationship between social support and psychological well-being in final year students in Bukittinggi City.